Impact of the Drug Loading Method on the Drug Distribution and Biological Efficacy of Exosomes - Kumar D.N.; Chaudhuri A.; Kumar D.; Singh S.; Agrawal A.K. (My University, 2025)
Exosomes are biological nanovesicles that are intrinsically loaded with thousands of biomacromolecules and are principally responsible for cell-to-cell communication. Inspired by the natural payload, they have been extensively investigated as drug delivery vehicles; however, the drug distribution, whether into or onto exosomes, is still debatable. In the present work, we have tried to investigate it systemically by selecting 5-fluorouracil (5-FU) (hydrophilic) and paclitaxel (PAC) (hydrophobic), drugs with very different physicochemical characteristics, for the loading to the exosomes. Exosomes were obtained from bovine milk, and the drugs were loaded using three different methods: incubation, sonication, and triton x-100. The particle size was found to be approximately 100 nm in all the cases; however, the highest drug loading was found in the sonication method. Fluorescence spectrophotometer, EDX analysis, EDX mapping, XPS, and XRD analysis indicated the possible presence of more drugs over the surface in the case of the incubation method. Drugs loaded by the sonication method had more controlled release than simple incubation and triton x-100. The method of drug loading had an insignificant effect on the cytotoxicity while in line with our previous observation, the combination (PAC and 5-FU) exhibited synergism as evidenced by ROS assay, colony formation assay, and mitochondrial membrane potential assay. Graphical Abstract: [Figure not available: see fulltext.]. © 2023, The Author(s), under exclusive licence to American Association of Pharmaceutical Scientists.